Фінансування аграрного сектору: синергетичний ефект стратегічного планування - Анастасова, К. А.; Почерніна, Наталя Вікторівна; Почернина, Наталья Викторовна; Pochernina, Natalia (My University, 2017)
UK: У статті проаналізовані сучасні проблеми фінансування аграрної сфери України. Розкрито механізм горизонтальної інтегрованості планування розвитку аграрного сектору та його синергетичний потенціал. Визначено напрями підвищення ефективності фінансування сільського господарства на регіональному рівні. EN: The detection of mechanisms of stabilization of the system in the conditions of its nonlinear dynamic development is an important task of anti-crisis regulation for subjects of management. The agrarian sector in recent years demonstrated a high level of resilience compared to other sectors of the real sector of the Ukrainian economy. Therefore, the analysis of both the most restrictive factors of its development and the stabilizers are quite relevant. The purpose of this article is to reveal the synergetic effect of strategic planning in order to increase the efficiency of financing of the agricultural sector in Ukraine. The objectives of the study are: analysis of the current problems of the agrarian sector development in Ukraine and the search for ways to overcome them; disclosure of the synergistic effect of horizontal integration of agrarian sector development planning; definition of directions for increasing the efficiency of agricultural financing at the regional level.
Аgricultural sector financing: sinergistical effect of the strategic planning
Keywords: аграрний сектор; фінансування; стратегічне планування; синергетичний ефект; регіон; ефективність; agricultural sector; financing; strategic planning; synergetic effect; region; efficiency